The Relationship between Work Motivation, Job Satisfaction, and Employee Performance: The Moderating Role of Psychology Capital and The Mediating Role of Organizational Commitment - Windu Astuti; Lia Amalia (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
This study aims to determine the effect of work motivation, organizational commitment, and job satisfaction on employee performance. The effect of organizational commitment mediates the relationship between work motivation on employee performance and job satisfaction on employee performance and psychological capital, which moderates the relationship between job satisfaction and employee performance. The object of this research is the employees of the state civil apparatus. They work in government agencies in the education sector of the Directorate of Senior High Schools in Jakarta. This study uses a quantitative approach with one hundred and ten respondents, sampling using a saturated sample technique, and a questionnaire as a measuring tool. Data analysis used the Structural Equation Modeling (SEM) method to test the model's suitability in this study with the help of the SmartPLS version 3 application. The results of this study conclude that work motivation, organizational commitment, and job satisfaction affect employee performance, organizational commitment can mediate the relationship between job satisfaction and employee performance but cannot mediate the relationship between work motivation and employee performance, and psychological capital can moderate the relationship between job satisfaction with employee performance.